A Non-Randomised Controlled Study of Interventions Embedded in the Curriculum to Improve Student Wellbeing at University - Rebecca Upsher; Zephyr Percy; Anna Nobili; Juliet Foster; Gareth Hughes; Nicola Byrom (MDPI AG, 2022)
Universal and preventative interventions are advocated via the curriculum and pedagogy to help overcome the increasing prevalence of poor mental health among university students. To date, the literature in this field is overall of poor quality and cannot be synthesised for meta-analysis, due to poor reporting of methodology and results, lack of control conditions, and mixed outcomes across studies. This study examines the effectiveness of curriculum-embedded interventions on student wellbeing at university. A non-randomised design compared four curriculum-embedded interventions with matched controls from the same cohort (Psychology, English, Nursing, International Politics). To increase power, a meta-analytic approach combined the conditions to examine improvements in student wellbeing, social connectedness, loneliness, students flourishing, self-compassion, burnout, self-esteem, and learning approach. There were non-significant improvements in the intervention versus control conditions across all outcomes. There is no strong support for curriculum-embedded interventions improving student wellbeing at university. Despite improvements in study design and reporting, the sample size was still a challenge. More studies of high quality need to be conducted to provide evidence to guide teaching staff in supporting student wellbeing in the curriculum. Qualitative research is required to fully understand students' experiences.